Association of tryptophan pathway metabolites with mortality and effectiveness of nutritional support among patients at nutritional risk: secondary analysis of a randomized clinical trial - Ritz, Jacqueline; Wunderle, Carla; Stumpf, Franziska; Laager, Rahel; Tribolet, Pascal; Neyer, Peter; Bernasconi, Luca; Stanga, Zeno; Mueller, Beat; Schuetz, Philipp (Frontiers in Nutrition, 2024)
An accelerated breakdown of the essential amino acid tryptophan to kynurenine, serotonin, and other metabolites may contribute to adverse outcomes during severe illnessTryptophan is an essential amino acid and is the precursor of many important metabolites and neurotransmitters. . In malnutrition, the availability of tryptophan is reduced, potentially putting patients at increased risks. Herein, we investigated the prognostic implications of the tryptophan metabolism in a secondary analysis of the Effect of Early Nutritional Support on Frailty, Functional Outcomes, and Recovery of Malnourished Medical Inpatients Trial (EFFORT), a randomized, controlled trial comparing individualized nutritional support to usual care in patients at risk for malnutrition. Among 238 patients with available measurements, low plasma levels of metabolites were independently associated with 30-day mortality with adjusted hazard ratios (HR) of 1.77 [95% CI 1.05-2.99, p 0.034] for tryptophan, 3.49 [95% CI 1.81-6.74, p<0.001] for kynurenine and 2.51 [95% CI 1.37-4.63, p 0.003] for serotonin. Nutritional support had more beneficial effects on mortality in patients with high tryptophan compared to patients with low tryptophan levels (adjusted HR 0.61 [95% CI 0.29-1.29] vs. HR 1.72 [95% CI 0.79-3.70], p for interaction 0.047). These results suggest that sufficient circulating levels of tryptophan might be a metabolic prerequisite for the beneficial effect of nutritional interventions in this highly vulnerable patient population.Groups based on high or low metabolite plasma levels. Data are number of events (%). *HR and *OR were adjusted for comorbidity, age, sex, randomization group and Nutritional Risk Screening 2002 total score. CI = confidence interval. HR = hazard ratio. IDO = indoleamine 2,3-dioxygenase. OR = odds ratio. TPH = tryptophan hydroxylase.